Personality factor and environmetal support influence success of women entrepreneurs in Kelantan: entrepreneurial intention as a mediator - Nur Sha Azelda Hashim (2018)
Malaysian economic growth and personal propensity to get involved with business show that women entrepreneurs have recently become the most important pool of resources. The increasing number of women’s involvement in entrepreneurship has escalated the success of women entrepreneurs, especially in Malaysia. This study examines the mediating effect of entrepreneurial intention on personality factors and environmental supports towards the success of women entrepreneurs in Kelantan. This study uses data set taken from 148 respondents that have been running their businesses for 3 years and above. The study uses Statistical Package for Social Science (SPSS) software to analyse the relationships between all the variables. The results showed that the personality factors and environmental supports are significantly positive to the success of women entrepreneurs. However, the result of mediator indicated that entrepreneurial intention was partially segregated into personality factors and environmental supports. This study supports the findings of the personality factors and environmental supports on the success of women entrepreneurs as conducted before. Therefore, future research should continue this study by adding relevant dimensions and components which are more appropriate to the field of study. Furthermore, the detailed personality factors in this study are potential reference for the planning of main or general education courses in the entrepreneurial field, especially to women. With the support from other organisation in financing and providing programmes to train the potential entrepreneurs among women will help to increase women’s involvement in entrepreneurial activities and being successful women entrepreneurs in the future.